N‐3 polyunsaturated fatty acids provoke a specific transcriptional profile in rabbit adipose‐derived stem cells in vitro. Issue 3 (28th February 2019) - Vackova, Eкaterina; Bosnakovski, Darko; Bjørndal, Bodil; Yonkova, Penka; Grigorova, Natalia; Ivanova, Zhenya; Penchev, Georgi; Simeonova, Galina; Miteva, Lyuba; Milanova, Anelya; Vachkova, Tatyana; Stanilova, Spaska; et al.
Abstract: Adipose‐derived stem cells (ADSCs) possess multipotent properties, and their proper functionality is essential for further development of metabolic disorders. In the current study, we explored the impact of two n‐3 LC‐PUFAs (long‐chain polyunsaturated fatty acids, DHA—docosahexaenoic; C22:6, and EPA—eicosapentaenoic; C20:5) on a specific profile of lipolytic‐related gene expressions in the in vitro ‐ differentiated subcutaneous and visceral ADSCs from rabbits. The subcutaneous and visceral ADSCs were obtained from 28‐day‐old New Zealand rabbits. The primary cells were cultured up to passage 4 and were induced for adipogenic differentiation. Thereafter, the differentiated cells were treated with 100 µg EPA or DHA for 48 hr. The total mRNA was isolated and target genes expression evaluated by real‐time RCR. The results demonstrated that treatment of rabbit ADSCs with n‐3 PUFAs significantly enhanced mRNA expression of Perilipin A, while the upregulation of leptin and Rab18 genes was seen mainly in ADSCs from visceral adipose tissue. Moreover, the EPA significantly enhanced PEDF (Pigment Derived Epithelium Factor) mRNA expression only in visceral cells. Collectively, the results suggest activation of an additional lipolysis pathway most evident in visceral cells. The data obtained in our study indicate that in vitro EPA up‐regulates the mRNA expression of the studied lipolysis‐associated genes stronger than DHA mainly in visceral rabbit ADSCs.